Machine Learning, Optimization, and Data Science: 5th International Conference, LOD 2019, Siena, Italy, September 10-13, 2019, Proceedings - Nicosia, Giuseppe; Pardalos, Panos; Umeton, Renato; Giuffrida, Giovanni; Sciacca, Vincenzo (Lecture Notes in Computer Science, 2020)
This book constitutes the post-conference proceedings of the 5th International Conference on Machine Learning, Optimization, and Data Science, LOD 2019, held in Siena, Italy, in September 2019. The 54 full papers presented were carefully reviewed and selected from 158 submissions. The papers cover topics in the field of machine learning, artificial intelligence, reinforcement learning, computational optimization and data science presenting a substantial array of ideas, technologies, algorithms, methods and applications.